Literature Review : Development of Monoclonal Antibodies Using The Expression System of Nicotiana benthamiana - Anugraheni, Audina Filsa Nur; Nuralyza, Imasayu; Maulira, Dinda Ayu; Ramadhani, Aliza Salsabila; Nugrahani, Baiq Dwiyan; Sunarwidhi, Anggit Listyacahyani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Monoclonal antibodies (mAbs) have become a key component in modern biotechnology and healthcare, playing essential roles in the treatment of diseases such as cancer, viral and bacterial infections, asthma, and in diagnostic applications. However, conventional mAb production using mammalian cell systems is costly, time-consuming, and presents scalability limitations. To address these challenges, current technological advances have led to the development of alternative platforms using plant-based expression systems. This review aims to explore the potential and progress in producing monoclonal antibodies through the Nicotiana benthamiana plant-based expression system, which offers several advantages including rapid production, cost efficiency, greater production capacity, and reduced risk of contamination. The method employed in this review is a literature study conducted through database searches (Google Scholar, PubMed, Science Direct, and others) focusing on peer-reviewed articles from 2015 to 2024. The articles were selected and then analyzed thematically was performed to extract relevant data. The results indicate that Nicotiana benthamiana can efficiently produce functional mAbs with glycosylation profiles comparable to mammalian systems. In addition, plant antibodies have also been successfully applied in various therapeutic and diagnostic studies. Further research is needed to ensure the safety and effectiveness of Nicotiana benthamiana plant-based mAb, as well as efforts to develop production scale for wider medical applications.